Lower third molar displaced to lateral pharyngeal space after mandibular angle fracture: a case report - dos Santos Pereira, Rodrigo [UNESP]; da Silva, Jonathan Ribeiro [UNESP]; Bonardi, João Paulo [UNESP]; Hochuli-Vieira, Eduardo [UNESP] (My University, 2018)
The removal of displaced dental elements from deep anatomical spaces is a condition that requires the knowledge of the region and skills to perform the procedure. The lateral pharyngeal space contains important structures such as the internal carotid artery and close proximity with the cranium basis. The aim of this paper is to report a clinical case of a lower third molar displaced to the lateral pharyngeal space after a mandibular angle fracture and its treatment by surgical intervention. The tooth was removed under general anesthesia by direct approach and the fracture was reduced and fixed with a plate and screws. This case report illustrates the importance of an immediate procedure to avoiding severe complications and further damage to important anatomical structures.
Keywords: Impacted tooth; Mandibular fractures; Molar; Third